Anticonvulsant Action of Monoamine Oxidase Inhibitors - Rioja Ugaz, Luis G. (1965)
For the evaluation of anticonvulsant drugs have been used a number of experimental methods with more mixed results. One technique that has shown good correlation with clinical anticonvulsant efficacy is based on the ability of certain drugs to alter the nature of the crisis produced by the supramóximo electroshock ( 12). The fact that classical anticonvu1sivantes barbiturates and hydantoins, anticonvulsants exert their protective effects , sedation accompanied by central nervous system , has remained the concern of researchers to find the ideal anticonvulsant. Studies by Prockop et al. in 1959 , have shown that monoamine oxidase (MAO ) in rats prevents presentation phase hindlimb tonic extension , produced by supramaximal electric shock . Unlike classical anticonvuIsivantes monoamine oxidase inhibitors have psicoanalépticas qualities (29).